The Proximal Effect of Alcohol on Intimate Partner Violence: Comparing the Antecedents of Intoxicated and Sober Men’s Violent Acts - Babcock, Julia C. (Journal of interpersonal violence, 2022)
Alcohol use is known to correlate with intimate partner violence (IPV) perpetration, yet little research examines how alcohol influences how the violence unfolds. The current study used sequential analysis to examine descriptions of past violent incidents and explore the behaviors that preceded men?s perpetration of IPV. In accordance with the alcohol myopia model of alcohol use, it was hypothesized that intoxicated men would respond violently to a wide range of partner cues, whereas men who were sober would only react violently in response to the most threatening partner cues. Moreover, intoxicated men were expected to demonstrate less inhibition of violence to suppressor cues of the partners? distress as compared to sober men. Participants were 80 couples reporting male-to-female IPV within the past year. Female partners? descriptions of two past violent events were coded and entered into sequential analysis. Antecedents to the men?s first violent action were examined. While sober men were likely to react violently to their partner?s physical threat and perceived threat, intoxicate men did not. Sober men were less likely to become violent after their partners displayed distress cues, whereas there was no suppressor effect of women?s distress for intoxicated men. The precursors of the violence of intoxicated men appears to be indiscriminate and unpredictable. Clinical interventions that rely on behavioral strategies or communication skills training are unlikely to be effective for those who have an unmanaged alcohol use disorder.